A SUDDEN SURPRISE OF THE SOUL: THE PASSION OF WONDER IN HOBBES AND DESCARTES - Deckard, Michael Funk 19XX- (Heythrop journal, 2008)
Philosophy begins in wonder, according to Plato and Aristotle. However, they did not expand a great deal on what precisely wonder is. Does this fact alone not raise curiosity in us as to why this passion is important? What is its role in our thinking except to end as soon as one begins conceptually delimiting its nature? The thinkers Thomas Hobbes and René Descartes both expanded upon earlier brief articulations of wonder in natural, supernatural and practical ways. By means of an historical and philosophical examination of these two early modern thinkers, this article hopes to begin to answer the question: ‘What is wonder?’